Method for characterizing extracellular proteins from the cell wall proteome of the copper tolerant fungus Phialophora malorum. (October 2019) - Daniel, Geoffrey; Volc, Jindrich; Halada, Petr; Karunasekera, Hasanthi; Kim, Jong Sik
Abstract: Phialophora malorum is a well-known copper tolerant fungus causing soft rot decay of copper-treated wood in-service in ground contact situations worldwide. The aim of the present work was to develop a method that allowed studies of the mechanism(s) behind extracellular copper tolerance by examining the profile of proteins expressed by P. malorum in the cell wall/slime (subproteome) environment in mycelia grown in Cu-supplemented media. The study involves development of a novel non-destructive approach using mild extraction, concentration, separation (SDS-PAGE electrophoresis) and characterization (MALDI-TOF MS/MS) of the proteins present. Studies revealed differential protein profiles and expression in Cu-supplemented (0.1% CuSO4 ) vs control shake cultures after 10 days growth. Twelve proteins including several hydrolytic (i.e. glucosidases, pectinase, polygalacturonase) enzymes were either unique or over-expressed in Cu-cultures compared to controls. The cell wall location of the proteins was consistent with a role in copper tolerance and detoxification by binding Cu-ions extracellularly. Several of the proteins (e.g. hydrolases, pectinase) are also involved in wood cell wall biomineralization. It is proposed that the concentration of metabolites (organic acids) slowly released in close vicinity of hyphal surfaces by weakly bound enzymes over-expressed through Cu-stress may function to reduce levels of free non-chelated Cu (II) ions entering the cell cytoplasm and therefore provide a first level of defense against copper toxicity. Highlights: Specific method for extracting/characterizing extracellular fungal cell wall/slime proteins developed. Method based on SDS-PAGE protein profiling and MALDI-TOF MS/MS characterization of polypeptides. Twelve proteins were either unique- or over expressed in Cu-grown cultures of P. malorum . Hydrolytic enzymes in the cell wall subproteome may provide Cu-tolerance by binding Cu-ions.